2017
DOI: 10.1007/s12160-017-9915-z
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Heart Rate Variability Reactivity and Trait Worry Interact to Predict the Development of Sleep Disturbances in Response to a Naturalistic Stressor

Abstract: This study supports the role of HF-HRV reactivity as a vulnerability factor for stress-induced sleep disturbances. The combination of high trait worry and high HF-HRV reactivity to worry might identify a subgroup of individuals most vulnerable to stress-related sleep disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 137 publications
(175 reference statements)
0
18
0
Order By: Relevance
“…Study authors were emailed to request supplementary results or data where clear associations were not reported, or if clarification was required as per the inclusion criteria (e.g., confirming whether samples referred to as "students" exclusively comprised undergraduate students. Ten of the 34 [29,[35][36][37][38][39][40][41][42][43] studies were included after study authors provided clarifications, statistics, or additional data by email.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study authors were emailed to request supplementary results or data where clear associations were not reported, or if clarification was required as per the inclusion criteria (e.g., confirming whether samples referred to as "students" exclusively comprised undergraduate students. Ten of the 34 [29,[35][36][37][38][39][40][41][42][43] studies were included after study authors provided clarifications, statistics, or additional data by email.…”
Section: Resultsmentioning
confidence: 99%
“…Details of study characteristics are presented in Table 1 and included a total of n=14,704 undergraduate student participants. The majority of the studies were cross-sectional (n=32) with only two longitudinal studies [37,42] including one intervention study [37]. All studies except one [44] reported mean age and standard deviation of the participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, larger decreases in vmHRV during a social‐evaluative stressor predict poorer performance on post‐stressor measures of inhibitory control (Roos et al, ). Larger reductions in response to a worry induction predict development of emotional distress and sleep disturbance during periods of academic stress (Gouin, Deschenes, & Dugas, ; MacNeil et al, ). These findings support the view that larger reductions in vmHRV in response to emotionally evocative challenges are associated with a broad vulnerability factor (Beauchaine & Thayer, ), but this may vary across types of adjustment difficulties (Beauchaine et al, ).…”
Section: Empirical Findingsmentioning
confidence: 99%
“…However, some inconsistent findings have been reported. One study with undergraduate students found that greater reductions in high-frequency HRV (another measure of PNS activity analogous to RSA) in response to worry induction was related to more sleep disturbances over the course of a semester (MacNeil et al, 2017). Another study found that less RSA withdrawal was associated with less activity during sleep for 9-year-old children, in the context of maternal depression (Keller et al, 2014).…”
Section: Pns and Sleepmentioning
confidence: 99%